Short- and long-term responses of nematode communities to predicted rainfall reduction in Mediterranean forests. (April 2023) - Homet, Pablo; Ourcival, Jean-Marc; Gutiérrez, Eduardo; Domínguez-Begines, Jara; Matías, Luis; Godoy, Oscar; Gómez-Aparicio, Lorena
Abstract: Climate change is a fundamental process affecting terrestrial ecosystems. However, there is relatively little knowledge about its impacts on soil communities, with a large degree of uncertainty regarding their resistance to predicted alterations in temperature and, particularly, precipitation. Moreover, most studies exploring the response of soil biota to predicted rainfall reduction have focused on mesic environments and soil microbes, which limit our ability to find general patterns across ecosystems and soil organisms. In this study, we analysed the impact of predicted climate change scenarios of rainfall reduction on soil food webs of Mediterranean water-limited forests using nematodes as bioindicators. We took advantage of replicated rainfall exclusion infrastructures (30% exclusion) established in Quercus forests of southern Spain in 2016 (2-year exclusion) and of southern France in 2003 (15-year exclusion) to explore the sensitivity of the soil food web to predicted reductions at short- and long-term scales. Rainfall reduction had large negative short-term effects on nematode abundance, particularly of lower trophic groups (bacterivores and fungivores). Rainfall reduction had also consistent short- and long-term impacts on community composition (decrease of fungivores, marginal increase of omnivores) and nematode-based indicators of soil food web structure (higher maturity and structure index, lower prey:predator ratio). These results can be considered indicative of a low resistance of the soil food web to rainfall reductions predicted by climate change. Overall, our findings demonstrate the sensitivity of water-limited forests to further reductions in soil water availability, which might substantially alter their soil communities and likely affect the many ecosystem processes that they control. Graphical abstract: Image 1 Highlights: Rainfall reduction had large negative short-term impacts on nematode abundance. Negative effects of rainfall reduction mainly affected lower trophic levels. Rainfall reduction had short- and long-term impacts on community composition. Rainfall reduction modified nematode-based indicators of soil food web structure. Soil nematodes in Mediterranean forests show high sensitivity to a drier climate.